2022
DOI: 10.3390/ijms232315327
|View full text |Cite
|
Sign up to set email alerts
|

The Anaphase-Promoting Complex/Cyclosome Is a Cellular Ageing Regulator

Abstract: The anaphase-promoting complex/cyclosome (APC/C) is a complicated cellular component that plays significant roles in regulating the cell cycle process of eukaryotic organisms. The spatiotemporal regulation mechanisms of APC/C in distinct cell cycle transitions are no longer mysterious, and the components of this protein complex are gradually identified and characterized. Given the close relationship between the cell cycle and lifespan, it is urgent to understand the roles of APC/C in lifespan regulation, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 160 publications
0
3
0
Order By: Relevance
“…According to Hu et al. [ 45 ], the anaphase-promoting complex/cyclosome (APC/C) is a novel cellular aging regulator based on its indispensable role in the regulation of lifespan and its involvement in age-associated diseases of eukaryotic organisms. This consistency reinforces the results.…”
Section: Resultsmentioning
confidence: 99%
“…According to Hu et al. [ 45 ], the anaphase-promoting complex/cyclosome (APC/C) is a novel cellular aging regulator based on its indispensable role in the regulation of lifespan and its involvement in age-associated diseases of eukaryotic organisms. This consistency reinforces the results.…”
Section: Resultsmentioning
confidence: 99%
“…There is ample evidence supporting the idea that normal APC activity protects against cancer development. Many APC subunit mutations have been identified in a variety of spontaneous human cancers [19,21,51,52], which can cause cells to survive exposure to chemotherapy (acquired resistance); mutations in at least 7 different APC subunits have been associated with resistance to spindle assembly checkpoint inhibitors [11]. It has been observed that APC impairment is associated with an extended duration of mitosis, allowing time for increased DNA repair, for suppression of chromosome segregation errors, and avoidance of mitotic catastrophe [19], thus providing a rational mechanism whereby malignant cell populations survive cytotoxic chemotherapy exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism whereby impaired APC activity may contribute to cancer development, aggressive behavior, and treatment resistance may be due to the failure of pro-oncogenic APC substrates to be appropriately degraded, resulting in a cancer-promoting environment. Multiple APC substrates are known to contribute to cancer development and progression, and have repeatedly been found to be elevated in many cancers, presumably due to reduced APC function and blunting of its E3 activity to target and clear them via ubiquitin-dependent proteasomal degradation (see [20,51] and references therein). APC-targeted proteins, such as CDC20, Securin, HURP, FOXM1, PLK1, and the Aurora kinases, accumulate in multiple unrelated cancer types and are generally associated with more aggressive disease and worse clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%